Study the Effect of Cerium Oxide Nanoparticles on Hematological Parameters and Liver Tissue in Rats by two Different ways: Oral Administration and Intravenous Injection - Maab Turki (Wasit Journal for Pure Sciences)
The objective of this work was to examine the acute toxic effects of cerium oxide nanoparticles (CeO2 NPs) on adult male white rats and comparison between orally administration and injection. Fifty experimental animals were randomly divided into two groups, the Orally group and the injection group, each group contains 4 Subgroup with 5 animals for each Subgroup as follows: Orally group: The first group T1 (as positive control group) that administrated 1 ml of distilled water, T2,T3,T4,T5 treated with CeO2 NPs with 50 mg\ml, 250 ml, 500 ml, and 1000 ml, respectively. In addition  Injection group:- T1 (as positive control group) and T2,T3,T4, T5, treated with 50 ml, 250 ml , 500 ml, and 1000 ml, of CeO2 NPs respectively. This study demonstrated no effect of CeO2 NPs on hematological parameters at p-value >0.05, While increase ALT and AST in both groups treated with of CeO2 NPs at p-value <0.05.  Furthermore cause congestion of the central vein with degeneration of hepatocytes in T4. While in high dose don’t show any effect. This study simultaneously concluded the cytotoxic effect in low dose on liver tissue while no effect in high dose. Also this study concluded no  effect on hematological parameters.